2021
DOI: 10.26508/lsa.202101225
|View full text |Cite
|
Sign up to set email alerts
|

Electron cryo-tomography structure of axonemal doublet microtubule from Tetrahymena thermophila

Abstract: Doublet microtubules (DMTs) provide a scaffold for axoneme assembly in motile cilia. Aside from α/β tubulins, the DMT comprises a large number of non-tubulin proteins in the luminal wall of DMTs, collectively named the microtubule inner proteins (MIPs). We used cryoET to study axoneme DMT isolated from Tetrahymena. We present the structures of DMT at nanometer and sub-nanometer resolution. The structures confirm that MIP RIB72A/B binds to the luminal wall of DMT by multiple DM10 domains. We found FAP115, an MI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 69 publications
6
32
1
Order By: Relevance
“…3A). This result is consistent with the fact that Enkur and Cfap52 are tightly embedded within the outer microtubule doublets of the axoneme (Gui et al, 2021; Li et al, 2022). The radial spoke protein Nme5 displayed similarly swift kinetics, extending at the same rate as the MIPs and the overall axoneme (Fig.…”
Section: Resultssupporting
confidence: 88%
“…3A). This result is consistent with the fact that Enkur and Cfap52 are tightly embedded within the outer microtubule doublets of the axoneme (Gui et al, 2021; Li et al, 2022). The radial spoke protein Nme5 displayed similarly swift kinetics, extending at the same rate as the MIPs and the overall axoneme (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Together with existing studies on MIPs (Ma et al, 2019) and the molecular rulers (Oda et al, 2014), our findings of the 96-nm repeat organization of Tetrahymena MIPs suggest that the periodicity of the inside and outside proteins/complexes can be self-regulated, probably through the head-to-tail interactions of the MIPs. Our finding showing that TtCFAP115 interacts with TtRIB72A/B is echoed by recent proteomics and low-resolution tomography studies (Fabritius et al, 2021; S. Li et al, 2022).…”
Section: Resultssupporting
confidence: 70%
“…The lack of the N-terminal region in PACRGB might explain why the inner junction of Tetrahymena is less stable upon salt treatment compared to Chlamydomonas (Khalifa et al, 2020), pointing to the role of the N-terminal fragment of PACRGA in the inner junction stabilization. We did not observe the unknown MIP densities observed from the subtomogram averaged map of Tetrahymena axonemal doublet (S. Li et al, 2022) (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Microtubule inner proteins (MIPs) are regularly distributed proteins that attach to the luminal side of the microtubule wall in cilia (Ichikawa et al, 2017; Kirima and Oiwa, 2018; Maheshwari et al, 2015; Nicastro et al, 2011; Nicastro et al, 2006), and in other hyperstable microtubule species, including subpellicular microtubules in apicomplexan parasites (Wang et al, 2021) and the ventral disc microtubules of Giardia (Schwartz et al, 2012). Many of the ciliary MIPs are highly conserved between species (Ichikawa et al, 2017; Khalifa et al, 2020; Ma et al, 2019; Maheshwari et al, 2015; Nicastro et al, 2011; Nicastro et al, 2006; Song et al, 2020), but some species-specific MIP features have also been reported, such as the Chlamydomonas beak-MIP (Dymek et al, 2019; Hoops and Witman, 1983), the T. brucei - specific B2, B4, B5, ponticulus MIPs, snake-MIP, ring MIP, and Ring Associated MIP (RAM) (Imhof et al, 2019), and a connection of MIP3 to the mid-partition in Tetrahymena (Li et al, 2022). Based on their locations and periodicities along the 96-nm repeat, we identified many conserved MIPs within S. rosetta ciliary doublet microtubules, including MIPs 1a, 1b, 2a, 2b, 2c, 3a, 3b, and 6a-d (Figure 4, A-F).…”
Section: Resultsmentioning
confidence: 99%